The Judiciary in Ajloun Province During the Mamluk Era (659-922 Ah / 1261-1516 Ad) - Al-Omari, Omar Saleh; ghnaimat, Qasem Mohammed; Bani Younes, Mohammad Ahmad (Dirasat: Human and Social Sciences, 2024)
Objective: This study aims to investigate the judiciary system in Ajloun Province during the Mamluk era by identifying the most prominent judges in that period and their achievements, whether in Ajloun and its administrative cities like Irbid and Hebras or other provinces such as Jerusalem, Hebron, Aleppo, Salt, Safed, Damietta, Baalbek, Homs, Tripoli and others. The study also sought to identify these judges’ place of birth and death. The focus extends from the Yarmouk River in the north, adjacent to the Damascus jurisdiction, to the Zarqa River in the south, bordered by the Balqa governorate on that side, and from the Shari’a River (Jordan) in the west to the eastern Badia region, all falling within the Ajloun district. Methods: The study followed a historical narrative and analytical approach to events, critiquing them. It relied on authentic historical sources, along with studies related to the study period, in addition to Arab research as listed in the sources and references. Results: The study revealed that Ajloun jurisdiction became a significant center for justice during the Mamluk era, attracting judges, some of whom were natives of the jurisdiction, while others came from outside. This includes areas they served within the jurisdiction like Irbid, and beyond the jurisdiction, such as Jerusalem, showcasing their judicial contributions until their passing. Conclusions: The Ajloun jurisdiction played a significant role in the Mamluk era, hosting judges who held prominent positions in major cities such as Damascus, Jerusalem, and Damietta.